(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article analyzes modern methods of organizing pre-medical first aid for sports injuries. Sports activities often involve a high risk of injuries that may significantly affect athletes’ health and performance. Therefore, providing immediate and appropriate first aid before professional medical assistance is crucial. The article examines common types of sports injuries, their causes, and modern approaches to providing pre-medical care. Special attention is given to injuries such as muscle strains, joint dislocations, fractures, and bruises that frequently occur during training sessions and competitions. The study also highlights the importance of modern technologies, emergency response systems, and the role of sports medicine specialists in ensuring effective first aid. In addition, the cooperation between coaches, medical staff, and sports organizations is discussed as a key factor in improving the quality of emergency care in sports environments. The findings indicate that well-organized pre-medical assistance significantly contributes to the prevention of complications and accelerates athletes’ recovery.